Silymarin Ameliorates Metabolic Dysfunction Associated with Diet-Induced Obesity via Activation of Farnesyl X Receptor - Gu, Ming; Zhao, Ping; Huang, Jinwen; Zhao, Yuanyuan; Wang, Yahui; Li, Yin; Li, Yifei; Fan, Shengjie; Ma, Yue-Ming; Tong, Qingchun; Yang, Li; Ji, Guang; et al. (Frontiers in Pharmacology, 2016)
Abstract BACKGROUND AND PURPOSE Silymarin, a standardized extract of the milk thistle seeds, has been widely used to treat chronic hepatitis, cirrhosis and other types of toxic liver damage. . Despite increasing studies on the action of silymarin and its major active constituent, silybin in their therapeutic properties against insulin resistance, diabetes and hyperlipidaemia in vitro and in vivo, the mechanism underlying silymarin action remains unclear. EXPERIMENTAL APPROACH C57BL/6 mice were fed high-fat diet (HFD) for 3 months to induce obesity, insulin resistance, hyperlipidaemia and fatty liver. These mice were then continuously treated with HFD alone or mixed with silymarin at 40 mg/100 g for additional 6 weeks. Biochemical analysis was used to test the serum lipid and bile acid profiles. FXR and NF-κB transactivities were analysed in liver using a gene reporter assay based onquantitative RT-PCR. KEY RESULTS Silymarin treatment ameliorated insulin resistance, dyslipidaemia and inflammation, and reconstituted the bile acid pool in liver of diet-induced obesity. Associated with this, silybin and silymarin enhanced FXR transactivity. Consistently, in HepG2 cells, silybin inhibited NF-κB signalling, which was enhanced by FXR activation. CONCLUSIONS AND IMPLICATIONS Our results suggest that silybin is an effective component of silymarin for treating metabolic syndrome by stimulating FXR signalling. Key words: silymarin; silybin; metabolic syndrome; non-alcoholic fatty liver disease; farnesyl X receptor Abbreviations ALT, alanine aminotransferase; AST, aspartate transaminase; BA, bile acid; DIO, diet-induced obesity; CA, cholic acid; DMSO, dimethylsulfoxide; FXR, farnesyl X receptor; HDL-c, high density lipoprotein cholesterol; HF, high-fat; IPITT, intraperitoneal insulin tolerance test; LDL-c, low density lipoprotein cholesterol; NAFLD, non-alcoholic fatty liver disease; NF-κB, nuclear factor kappa B; NR, nuclear receptor; MS, metabolic syndrome; Rosi, rosiglitazone; TBA, total bile acid; TC, total cholesterol; TCA, taurocholic acid; TCDCA, tauro-chenodeoxycholic acid; TG, triglyceride; TUDCA, tauro-ursodeoxycholic acid